Circular RNA circLGMN facilitates glioblastoma progression by targeting miR-127-3p/LGMN axis. (1st December 2021) - Chen, Binghong; Wang, Mengying; Huang, Renhua; Liao, Keman; Wang, Tianwei; Yang, Renhao; Zhang, Wenrui; Shi, Zhonggang; Ren, Li; Lv, Qi; Ma, Chunhui; Lin, Yingying; et al.
Abstract: Glioblastoma (GBM) is one of the most devastating cancers and is characterized by rapid cell proliferation and aggressive invasiveness. Legumain (LGMN), a substrate-specific protease, is associated with poor progression of GBM. Circular RNAs (circRNAs) are aberrantly expressed in various cancers and play crucial roles in tumor progression; however, the functional roles of circRNAs originating from LGMN remain largely unknown in GBM. Herein, we found that hsa_circ_0033009 (circLGMN) was the most abundantly expressed circRNA derived from LGMN . CircLGMN was upregulated in high-grade glioma (HGG), and high expression of circLGMN was associated with poor prognosis in patients with glioma. CircLGMN overexpression promoted GBM cell proliferation and enhanced cell invasion. Mechanistically, circLGMN acts as a sponge for miR-127-3p, and prevents miR-127-3p-mediated degradation of LGMN mRNA, ultimately leading to increased LGMN protein expression. Treatment with miR-127-3p mimic suppressed proliferation and reduced invasion of GBM cells overexpressing circLGMN. Moreover, circLGMN overexpression promoted GBM malignancy in vivo, while miR-127-3p overexpression alleviated this effect. Taken together, circLGMN is a novel tumor-promoting circRNA that acts by sponging miR-127-3p, which ultimately leads to LGMN upregulation. Thus, targeting the circLGMN/miR-127-3p/LGMN axis might be a promising strategy for GBM treatment. More importantly, the discovery of the self-regulatory mechanism of LGMN expression by circLGMN, will facilitate further research on LGMN. Highlights: CircLGMN is high expression in glioma and is associated with poor prognosis of patients with glioma. Upregulation of circLGMN dramatically elevates the expression of LGMN, especially the intermediated form. CircLGMN can sponge for miR-127-3p and disengage the latter from degradation of LGMN. CircLGMN promotes GBM progress in vitro and in vivo, these effects are inhibited by miR-127-3p.